The cosmopolitan state - Glenn, H. Patrick (Oxford : Oxford University Press, 2013)
The idea of the 'nation-state' has failed, Glenn argues, and a major shift in our understanding of the state is needed. He provides an original approach by situating cosmopolitanism in its historical context and demonstrates that the state is necessarily cosmopolitan in character, and has always been subject to transnational law-making.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 1, 2013).
Keywords: Constitutional law; Cosmopolitanism; State, The